Firefly Optimization in IOT Applications for Wireless Mesh Networks - et. al., Dr.Shaji. K. A. Theodore M. Samira , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Internet of Things is an budding focus of technical, social, and economical importance. At the same time, Internet of Things hoist momentous challenges that may perhaps plunk in the way of apprehend its prospective reimbursement. The ‘thing’ in IoT may perhaps be a person with a heart monitor or an automobile in the midst of built-in-sensors, i.e. objects that have subsist dole out an IP address and encompass the capability to accumulate and convey data over a network without manual assistance or intervention. The business processes hosted on the wide-spread geographical distribution of sensors should retort to dissimilar sensing events congregate in the dynamic IoT environment as swift as they could. So to Produce better IoT applications, process optimization is indispensable in the IoT environment. For example, data analytics in energy embarrassed IoT Networks uses Optimization Framework to recuperate the network implementation delay and accuracy. Here we imply firefly Optimization Algorithm Framework, wherever the nodes make a decision where their data analytic tasks will be executed, in order to jointly optimize their average execution delay and accuracy, while respecting power consumption constraints compared to previous other techniques. Our new fire fly optimization techniques shows 81% better results compared to previous techniques such as Genetic and ant colony etc…